Acute Kidney Injury: The Role of Biomarkers for Early Diagnosis. Issue 2 (April 2016) - Lentini, Paolo; De Cal, Massimo; Zanoli, Luca; Granata, Antonio; Dell'Aquila, Roberto
Acute kidney injury is an important health problem and its incidence is increasing. Acute kidney injury has traditionally been measured and defined using surrogate measurements of the function of renal filtration, as plasma creatinine and urea. Despite the serious delay in diagnosing acute kidney injury, creatinine remains the most used biomarker. In recent years, clinicians highlighted the need to find new biomarkers for acute kidney injury that can replace or implement the data found using creatinine and that can allow an early measurement of the damage. Despite the multiple biomarkers analyzed and tested in recent years, creatinine is the reference marker because it is easy to measure and for its lower costs. Biomarker panels, employed in various frames help to determine the beginning and the duration of kidney damage or the severity of acute kidney injury, may assist in the diagnosis of acute kidney injury.